Functional Connectivity Architecture of the Human Brain: Not All the Same. (October 2014) - Wang, Danhong; Liu, Hesheng
Imaging studies suggest that individual differences in cognition and behavior might relate to differences in brain connectivity, particularly in the higher order association regions. Understanding the extent to which two brains can differ is crucial in clinical and basic neuroscience research. Here we highlight two major sources of variance that contribute to intersubject variability in connectivity measurements but are often mixed: the spatial distribution variability and the connection strength variability. We then offer a hypothesis about how the cortical surface expansion during human evolution may have led to remarkable intersubject variability in brain connectivity. We propose that a series of changes in connectivity architecture occurred in response to the pressure for processing efficiency in the enlarged brain. These changes not only distinguish us from our evolutionary ancestors, but also enable each individual to develop more uniquely. This hypothesis may gain support from the significant spatial correlations among evolutionary cortical expansion, the density of long-range connections, hemispheric functional specialization, and intersubject variability in connectivity.